1996
DOI: 10.1016/0167-2789(96)00018-8
|View full text |Cite
|
Sign up to set email alerts
|

Generalized scaling in fully developed turbulence

Abstract: --

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
150
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 28 publications
14
150
0
Order By: Relevance
“…By contrast, a similar form of scaling does not seem to hold for the structure function of a passive scalar transported by turbulence [2]. This indicates that General Scaling is representative of a fundamental property of velocity increments.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…By contrast, a similar form of scaling does not seem to hold for the structure function of a passive scalar transported by turbulence [2]. This indicates that General Scaling is representative of a fundamental property of velocity increments.…”
Section: Introductionmentioning
confidence: 80%
“…Recent studies, however, have raised up doubts about the validity of such scaling: for example, it is shown in [1] that the true scaling could rather be exp(ζ(n)a −1 a ) where a is inversely proportional to the Reynolds number. Given such controversy, the discovery by [2] of a new form of scaling is very interesting. This general form of scaling, named General Scaling, extends down to the smallest resolvable scale.…”
Section: Introductionmentioning
confidence: 99%
“…0, by a simple uncorrelated random cascade (5) and that their subleading contribution, r R ϳ O͑1͒, is fully captured by the geometrical constraint previously discussed, namely, the Ward identities.…”
mentioning
confidence: 99%
“…In [5] it has been discussed in detail whether the refined Kolmogorov hypothesis (RKH) for the energy dissipation is consistent with a random multiplicative process for the velocity increments. It has been shown that, at least on the synthetic signal, RKH is satisfied.…”
mentioning
confidence: 99%
See 1 more Smart Citation